Interpretasi Hakim Pengadilan Agama di Riau tentang Konsep Nusyuz dalam Perkawinan - Chintya, Aprina (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
Divorce is the cause of marriage breakdown according to the Islamic and Consitutional Law No. 1 of 1974 about marriage. When there is a marriage, the husband and wife both bear the rights and duties that must be fulfilled in order to build a sakinnah, mawaddah and rahmah family. When thay cannot execute their duties, it can be categorized as Nusyuz. The concept of Nusyuz is still very general and has various interpretation, depending on judge's views of who handles divorce cases in religious courts. It induces differences in defining and categorizing nusyuz among judges. This field research was conducted to discover judges' opinions at Riau religious court about the concept of nusyuz and what actions considered to be nusyuz. Observation and interview were employed to collect the data from judges and litigants purposively by using the socio-legal approach. The results of this research showed that Nusyuz means an act of wife which consciously disobey her obligation to her husband. In determining nusyuz, the judges also examined the action consideration.